2022
DOI: 10.2186/jpr.jpr_d_20_00276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tooth brush abrasion on the color, gloss and surface roughness of internally and externally stained monolithic ceramic materials

Abstract: Purpose: To measure the durability of the color, change in surface roughness and gloss of stained monolithic ceramic materials subjected to artificial tooth brush abrasion. Materials and methods: Standardized specimens were manufactured from pressable lithium-disilicate glass ceramic (PC; IPS e.max Press), machinable lithium-disilicate glass ceramic (MC; IPS e.max CAD), and zirconia (ZR; Zenostar). Ceramic staining was applied before (internal; in) and after crystallization/ sintering (external; ex). Of each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In the literature, surface roughness values are between 0.55 and 1.68 µm for IP 31 - 33 and 0.2 and 4.75 µm for IC. 34 - 38 In the current study, mean surface roughness values were 2.16 ± 1.15 µm for IP specimens and 2.52 ± 1.25 µm for IC specimens. Demir et al 34 reported that home bleaching applied with 16% carbamide peroxide for seven days increased the surface roughness of IPS e. max CAD specimens.…”
Section: Discussionsupporting
confidence: 42%
“…In the literature, surface roughness values are between 0.55 and 1.68 µm for IP 31 - 33 and 0.2 and 4.75 µm for IC. 34 - 38 In the current study, mean surface roughness values were 2.16 ± 1.15 µm for IP specimens and 2.52 ± 1.25 µm for IC specimens. Demir et al 34 reported that home bleaching applied with 16% carbamide peroxide for seven days increased the surface roughness of IPS e. max CAD specimens.…”
Section: Discussionsupporting
confidence: 42%
“…Moreover, Goudas et al examined the surface roughness of pressable dental ceramics after different aging conditions and reported that lower surface roughness values were observed [38]. On the contrary, previous studies showed that toothbrushing significantly increases surface roughness [13,39].…”
Section: Discussionmentioning
confidence: 99%
“…Toothbrushing, as an example of surface wear, is another main factor that might influence the surface properties of ceramic materials. Many studies [12][13][14][15] have reported that toothbrushing can adversely affect feldspathic porcelain restorations [12]. A previous study reported that extrinsically stained feldspathic porcelain restorations showed significant alteration in surface roughness and color after 8.5 years of simulated toothbrushing [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation